(untitled) (Research, Society and Development, 2025)
Introduction: Trigeminal neuralgia is a chronic neuropathic condition characterized by recurrent episodes of sudden, severe, unilateral facial pain resulting from hyperexcitability of trigeminal neurons, most often associated with neurovascular compression. This condition has a significant functional and emotional impact, requiring effective and well-tolerated therapies. Objective: To analyze the main recent advances in the pharmacological approach to trigeminal neuralgia, with an emphasis on therapeutic innovations, mechanisms of action, and future perspectives for clinical management. Methodology: This is an integrative review of the literature, both quantitative and qualitative in nature, structured in six methodological steps. The search was conducted between October and November 2025 in the PubMed, SciELO, Google Scholar, and Virtual Health Library databases, using the descriptors Trigeminal Neuralgia, Neuropathic Pain, Pharmacological Treatment, and Drugs. Studies published between 2020 and 2025 were included, resulting in 21 critically analyzed articles. Results: The consolidation of classic anticonvulsants, such as carbamazepine and oxcarbazepine, and the advancement of new agents, such as gabapentinoids, selective sodium channel blockers (Nav1.7), and anti-CGRP antibodies, were observed. Adjuvant therapies, such as botulinum toxin type A and photobiomodulation, are also noteworthy, in addition to the incorporation of pharmacogenomics and nanotechnology in personalized treatment. Conclusion: Pharmacotherapy for trigeminal neuralgia is moving toward safer and more targeted approaches, integrating innovative and combined therapies that increase pain control and improve patients’ quality of life.